2021
DOI: 10.3390/buildings11020057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Masonry Infill Constitutive Law on the Global Response of Infilled RC Buildings

Abstract: Masonry-infilled reinforced concrete frames represent a very common construction typology across the Mediterranean countries. The presence of infills substantially modifies the global seismic performances of buildings in terms of strength, stiffness, and energy dissipation. Although several research studies focused on the overall performances of infilled reinforced concrete frames, the modeling of infill panels remains an open issue due to the complex interaction between the infill and the frame and the uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The opening percentage is considered constant and equal to 20% of the area of the infill panel. The adoption of different opening percentages along the height also significantly influences the builing response and the distribution of lateral deformations (e.g., [21]- [22]). However, this effect is not investigated in this study.…”
Section: Model and Structural Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The opening percentage is considered constant and equal to 20% of the area of the infill panel. The adoption of different opening percentages along the height also significantly influences the builing response and the distribution of lateral deformations (e.g., [21]- [22]). However, this effect is not investigated in this study.…”
Section: Model and Structural Analysismentioning
confidence: 99%
“…Further, by keeping as a reference the panels with tw=24cm, the maximum scatter between different thicknesses is obtained for the AQK record in the transverse direction, at the third story, where a scatter of 76% in IDR value is achieved. The effect of infill thickness produces a significant variation of IDR [22], and thus of the potential damage experienced by drift-sensitive components.…”
Section: Model and Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that the maximum stress decreased with increasing temperature, and it increased with an increasing strain rate. These people established the constitutive models required for quantitative analysis based on experimental samples, but these have rarely been combined with CT experiments [9,[12][13][14][15][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%